Exploring the diffusion of tweets designed to raise the road safety agenda in Saudi Arabia. (December 2017) - Albalawi, Yousef A.; Sixsmith, Jane
This study demonstrates the importance of understanding the diffusion process in social media such as Twitter as an example of the relationship between new media platforms and health promotion interventions. Evidence-informed tweets were developed, pilot tested and distributed to all followers of the Ministry of Health's Twitter account with the aim of influencing the agenda on road safety in Saudi Arabia. The dissemination pattern and influence of this health communication was assessed. We collected 70 tweets into two groups (29 intervention tweets and 41 additional supported tweets) extracted from the Tweetreach data set and then analysed them using Microsoft Excel and SPSS. Using the concept of innovation/imitation as defined in the Bass Model, we classified retweeting by direct followers as innovation and retweeting by users who were not followers as imitation. In the study, we identify an informative indicator of successful diffusion and propose a novel procedure to measure innovation/imitation coefficients ( p and q ). We also provided a statistical procedure for evaluating tweet adoption by innovators (influentials) and imitators. In addition, we also assessed the use of message design tools for new media messages. The resulting information can be used to improve public health and health promotion interventions at the levels of planning, design, implementation and evaluation.